Optimal timing for intravascular administration set replacement - Ullman , Amanda; Rickard, Claire; O'Riordan, Elizabeth; McGrail, Matthew; Marsh, Nicole; Daud, Azlina; Gillies, Donna; Cooke, Marie (John Wiley & Sons, Ltd., 2013)
Background